Parents' Reasons for Sending Children to Pre-primary Schools: A Case of Kaskazini "˜A' District Zanzibar - Muhammed, Shehe; Mligo, Ignasia; Seni, Abdalla (African Journal of Education and Practice, 2023)
Purpose: This study explored parents' reasons for sending their children to pre-primary education in Zanzibar. The reasons are discussed with respect to their understanding of pre-primary education as a basic education in Zanzibar. Methodology: A qualitative approach with a case study design was used; data were collected using face-to-face interviews from 36 parents, 14 males and 22 females who had children in pre-primary schools. The study was done in the light of the Expectancy Value Theory (EVT) that relates the expectations and values a person has over something, and proposes that achievement behaviour is primarily influenced by expectancies of success and subjective task values. Findings: The results showed that most parents understood that early childhood education was a basic education in Zanzibar due to the fact that it is a starting point for children to learn basic life skills and literacy skills. Therefore, it was revealed that parents were sending their children to pre-primary schools because they wanted their children to be literates, prepared for primary education and learn socialization. It was revealed that early childhood education teaches children different skills like reading, writing, counting and socialization skills, and so changes a child from having a home-mind to school-mind. Unique Contribution to Theory, Practice and Policy: The study recommends to the curriculum developers to plan and design early childhood education programmes to achieve the targets of the parents so as to encourage them in sending their children to pre-primary education as well as increase their involvement in their children's education.